DINAMIKA PEMBELAJARAN DARING MELALUI BELAJAR DARI RUMAH (BDR) PADA PAUD MIFTAHUL ULUM SAAT PANDEMI COVID 19 - Nur Aisyah (Dar el-Ilmi : jurnal studi keagamaan, pendidikan dan humaniora, 2021)
The purpose of this study was to determine and analyze the dynamics of online learning through learning from home (LFH) in early childhood in Miftahul Ulum. Namely, it can be seen from 1) The Role of Parents in Early Childhood Education (PAUD) Online Learning from Home, and 2) Problems of online learning through learning from home. The method used in this research is qualitative with the object of research for early childhood students and parents who accompany online learning through learning from home. The results of the study found that the dynamics of online learning through learning from home were not easy for both teachers, students and parents. There are many obstacles faced, both in terms of the role of parents in accompanying or accompanying students at home and from the side of the teacher who are constrained in the process of observation and assessment for students.